2012
DOI: 10.1037/a0025515
|View full text |Cite
|
Sign up to set email alerts
|

Status conferral in intergroup social dilemmas: Behavioral antecedents and consequences of prestige and dominance.

Abstract: Bridging the literatures on social dilemmas, intergroup conflict, and social hierarchy, the authors systematically varied the intergroup context in which social dilemmas were embedded to investigate how costly contributions to public goods influence status conferral. They predicted that contribution behavior would have opposite effects on 2 forms of status-prestige and dominance-depending on its consequences for the self, in-group and out-group members. When the only way to benefit in-group members was by harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(151 citation statements)
references
References 79 publications
4
145
0
2
Order By: Relevance
“…Interacting more effectively with the empirical literature from related disciplines is yet another task for future work. Research results and methods from areas such as group dynamics (Jones, Carter-Sowell, & Kelly, 2011), social dilemmas (Balliet, 2010;Halevy, Chou, Cohen, & Livingston, 2012) and those derived from "cultural evolutionary theory" (Boyd & Richerson, 2005;Paciotti, Richerson, & Boyd, 2006;Whiten, Hinde, Laland, & Stringer, 2011) should be explored-an accomplishment that demands further conceptual, theoretical, and experimental analysis and synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interacting more effectively with the empirical literature from related disciplines is yet another task for future work. Research results and methods from areas such as group dynamics (Jones, Carter-Sowell, & Kelly, 2011), social dilemmas (Balliet, 2010;Halevy, Chou, Cohen, & Livingston, 2012) and those derived from "cultural evolutionary theory" (Boyd & Richerson, 2005;Paciotti, Richerson, & Boyd, 2006;Whiten, Hinde, Laland, & Stringer, 2011) should be explored-an accomplishment that demands further conceptual, theoretical, and experimental analysis and synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Dominant individuals were also found to signal their formidability by lowering their vocal pitch during the initial minutes of a group interaction, whereas those high in prestige do not systematically change their pitch (Cheng, Tracy, Ho, & Henrich, 2013). Individuals high in dominance versus prestige also demonstrate divergent hormonal (i.e., Testosterone) profiles (Johnson, Burk, & Kirkpatrick, 2007); patterns of economic decision making (Bruno, 2006;Halevy, Chou, Cohen, & Livingston, 2012); differential perceived attractiveness and desirability (Snyder, Kirkpatrick, & Barrett, 2008); and, in small-scale societies, reproductive success and nutritional health status (Reyes-Garcia et al, 2009;von Rueden, Gurven, & Kaplan, 2011). Collectively, these studies provide converging support for the claim that dominance and prestige are distinct and independent processes that simultaneously give rise to and underpin human rank relationships.…”
Section: The Dominance-prestige Account Of Social Rankmentioning
confidence: 99%
“…A dominant leader, by virtue of being perceived as decisive, assertive, self-assured, and determined to serve the interest of group members even at the cost to non-group members (16), is considered to be more reliable in motivating individual members to take swift collective action in the face of uncertainty (23). A prestigious leader, on the other hand, is generally perceived as a generous and helpful individual who therefore is reluctant to prioritize the interest of group members at all costs and especially at the expense of individuals outside the group (16); the prestigious leader thus appears to be less agentic or to be indecisive in making difficult decisions (18).…”
Section: Significancementioning
confidence: 99%
“…Evolutionary psychology further illustrates that primates, including humans, organize around dominance hierarchies with an alpha leader perched at the top, an organizational preference that is especially acute when the environment is uncertain or threatening or when there is contest among species or groups for resources (9,10,(14)(15)(16). For instance, a study found that after researchers transposed the central attributes of the faces of George Bush and John Kerry to a neutral face, participants preferred Bush's physiognomy, which they associated with greater masculinity, as their leader in times of war and Kerry's physiognomy, which they considered comparatively low on masculinity, as their leader in times of peace (15).…”
mentioning
confidence: 99%